EXPÉRIMENTER LA PENSÉE EN SCHÉMAS-IMAGES. DES ADOLESCENTS S’INTERROGENT « D’OÙ VIENNENT LES PENSÉES ? » - Anda FOURNEL; Jean-Pascal SIMON (Studia Universitatis Babeș-Bolyai. Philosophia)
Experimenting Thinking in Image Schemas. Teenagers are Wondering “Where Do Thoughts Come From?”. An intellectual view of philosophy as an activity focusing on understanding abstract concepts and their relationships deprives philosophical exercise of the participation of the body and senses. If we reject the mind-body dualism, as Dewey, Johnson, etc. did, then we are constantly engaged in interactions with the world and others, and can thus consider the act of thinking from our own experiences. Inspired by an experimentalist conception of school and life, as well as the method of inquiry developed by Dewey, the Philosophy for Children program provides an inquiry process that invites participants to conceptualize and reason philosophically in a collaborative manner. Do these practices implement an embodied cognition? To find out, we selected a discussion as a case study and analyzed it based on the observation that the issue to be discussed by the participants - “where do thoughts come from?” contains two image schemas: path (come from) and source (where). We have noted a variety and a significant number of expressions (“they come from within”, “they come from what happens outside”, etc.) whose analysis enhances a better understanding of how an experience of understanding the origins of our thoughts fits into the discourse and contributes to a collective conceptualization of “thinking”.